Caracterização clínica e sociodemográfica de pacientes com Covid-19 e avaliação da influência de polimorfismos no gene IFNAR2 na gravidade e no desfecho clínico da doença - Montenegro, Artur Fontenelle Lima (2023)
Coronavirus disease 2019 (COVID-19) is an infectious disease caused by SARS-CoV-2. Over 750 million cases and over 6 million deaths caused by this disease worldwide have been reported. Type I interferons (IFN-I) are molecules produced by virus-infected cells to alert neighboring cells of a virus infection. The IFN-I pathway plays a crucial role in the antiviral immune response and modifications in this pathway may affect disease severity. The advance in molecular biology techniques allows further investigation about the importance of host genetic variability for infectious diseases. The identification of sequence variation among populations can infer the association between genes and diseases. These genetic variations are denominated as genetic polymorphisms, which generally are the result of changes in a single nucleotide, known as single nucleotide polymorphisms (SNP). This study aims to analyze sociodemographic, clinical and genetic characteristics among COVID-19 patients. These patients were divided into groups according to disease severity (40 mild/moderate and 82 severe patients) and according to clinical outcome (49 survivors and 33 non-survivors). Whole blood samples were collected from these patients for laboratory tests between January and May 2021, resulting in 122 samples. ICU patients with desaturation or Acute Respiratory Distress Syndrome were considered severely ill. Information such as sex and age from the patients were available for all patients, therefore were submitted for data analysis, according to disease severity and clinical outcome. On the other hand, the comorbidities and symptoms were available only for severe patients, only being analyzed according to clinical outcome. To perform the genotyping assays the samples went through DNA extraction, purified DNA quantification and normalization of DNA concentration. The polymorphisms in the IFNAR2 gene, identified as rs2250226, rs2236757, rs2252650 and rs2284551, were genotyped. The relative frequency distribution of the sociodemographic, clinical or genetic characteristics was verified and then Fisher’s exact test was applied to seek for significant difference between groups. When Fisher’s exact test could not be performed, Pearson’s chi-squared was used instead. Statistical analysis showed that patient sex and age were significantly different between disease severity groups. On the other hand, none of the sociodemographic, clinical or genetic characteristics showed significant difference between clinical outcome groups, although some of their relative frequency distribution were different. There were no significant genotype difference between severity or clinical outcome groups for the variants studied. Therefore, these data indicate a higher disease severity risk for male patients and patients with age greater than or equal to 60, but no higher death risk was associated with the characteristics analyzed or genotypes of the rs2250226, rs2236757, rs2252650 and rs2284551 polymorphisms.